Modeling of cutting of stainless steel AISI 304 by abrasive water jet - Xiaojin Miao; Meiping Wu (Materials Research Express, 2020)
Abrasive water jet (AWJ) has distinct advantages in machining stainless steel, titanium alloy and other metals because of its high machining ability and cold working characteristics. In this paper, the depth of cutting stainless steel AISI 304 by abrasive water jet was studied, so as to provide guidance for reasonable setting of process parameters. Firstly, the effect mechanism of main process parameters on cutting depth was analyzed. Then, the simulation model was built by the method of SPH coupled FEM to simulate the erosion process of abrasive water jet. Then, the material removal volume was studied from the micro and macro perspectives. Based on the essential equivalent relationship between the two aspects, the parametric model of cutting depth was deduced. Finally, the two models were compared and verified. The results show that the parametric model can be used to predict the cutting depth of AISI 304 and guide the setting of process parameters.